Des pratiques professionnelles au fil de l’écriture - Carmen Strauss-Raffy (Éducation et Socialisation)
This article reports on a research project dealing with writing about professional practices. Special Needs teachers working within specialized networks in the French educational context (RASED) wrote for two years about their profession and its underpinnings within the framework of a monthly writing workshop focusing on the literary dimension. The impact of the writing practice of these teachers and their relationship to their profession is analyzed through interviews carried out with each participant about their own experience of the writing process.